2006
DOI: 10.1108/09544780610685485
|View full text |Cite
|
Sign up to set email alerts
|

Selection of six sigma projects in the UK

Abstract: PurposeThe literature suggests that a key ingredient for the successful six sigma implementation is project prioritisation and selection. The purpose of this paper is to identify what criteria are considered for selecting six sigma projects and how six sigma projects are selected in organisations in the UK.Design/methodology/approachUsing a survey as a method of investigation, respondents were asked what criteria are considered to select projects and how potential projects are identified, prioritised, selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
92
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 9 publications
2
92
0
3
Order By: Relevance
“…Antony (2006) states that the correct selection and prioritisation of projects is a key critical success factor in a Six Sigma programme, which suggests that organisations adopting this improvement approach are likely to use objective project prioritisation methods. This is supported by the results of a survey carried out by Banuelas et al (2006), which targeted large UK organisations implementing Six Sigma. The study found that almost all Six Sigma organisations in the study use at least one objective method for project prioritisation, with the most common being CBA and Pareto analysis, both of which are tools of Six Sigma (Sharma and Chetiya, 2010).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Antony (2006) states that the correct selection and prioritisation of projects is a key critical success factor in a Six Sigma programme, which suggests that organisations adopting this improvement approach are likely to use objective project prioritisation methods. This is supported by the results of a survey carried out by Banuelas et al (2006), which targeted large UK organisations implementing Six Sigma. The study found that almost all Six Sigma organisations in the study use at least one objective method for project prioritisation, with the most common being CBA and Pareto analysis, both of which are tools of Six Sigma (Sharma and Chetiya, 2010).…”
Section: Introductionmentioning
confidence: 73%
“…In this sense, Banuelas et al (2006) carried out a study to identify the criteria followed by UK organisations to prioritise Six Sigma improvement projects. The study found the most widely used tools by UK companies and the most common criteria they follow to prioritise improvement projects.…”
Section: Introductionmentioning
confidence: 99%
“…According to the research, about 60 percent of the companies identify potential projects from their customers. The critical factors in the selection of six sigma projects were determined as customer satisfaction, financial gains, linking with organization strategy and top management commitment (Banuelas et al,2006). Selection of six sigma projects is a very important stage.…”
Section: Six Sigma Projectsmentioning
confidence: 99%
“…Business entities should select Six Sigma projects in such a manner that they are directly attached to the targets and plans, since various productive areas of enhancement struggle for limited resources. Six Sigma project selection is one of the most commonly argued issue in the literature these days because most of the Six Sigma projects get failed due to improper selection of improvement projects (Banuelas et al, 2006). Project selection is the process of estimating individual projects, and then choosing most essential project to implement Six Sigma, so that the targets of the company will be accomplished.…”
Section: Introductionmentioning
confidence: 99%